2016
DOI: 10.5812/numonthly.38347
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aromatherapy on Anxiety in Patients

Abstract: BackgroundAnxiety is the most common mental disorder in end-stage renal disease patients. The use of aromatherapy as a treatment for anxiety has increased substantially in most countries.ObjectivesThis study aimed to investigate the effect of inhaling rose water aromatherapy on anxiety in hemodialysis patients.MethodsThis randomized controlled clinical trial was carried out in the hemodialysis ward of Birjand Vali-Asr hospital on 46 patients who were randomly divided into control and experimental groups. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 14 publications
5
39
1
7
Order By: Relevance
“…Although more precisely speaking, state anxiety scores showed a large size effect in comparison with trait anxiety scores that only exhibited medium size effect. This is in accordance with other studies which investigated the effectiveness of aromatherapy in reducing a state anxiety situation [11,32]. This may be due to the fact that state anxiety is related to temporary situations that change every moment, and when they disappear, the person no longer experiences anxiety; on the other hand, trait anxiety is related to particular and permanent personality features [33].…”
Section: Discussionsupporting
confidence: 75%
“…Although more precisely speaking, state anxiety scores showed a large size effect in comparison with trait anxiety scores that only exhibited medium size effect. This is in accordance with other studies which investigated the effectiveness of aromatherapy in reducing a state anxiety situation [11,32]. This may be due to the fact that state anxiety is related to temporary situations that change every moment, and when they disappear, the person no longer experiences anxiety; on the other hand, trait anxiety is related to particular and permanent personality features [33].…”
Section: Discussionsupporting
confidence: 75%
“…The findings of the current study were in line with the study conducted by Barati et al (2016) to study the effect of the aromatherapy with Damask Rose on the anxiety of hemodialysis patients and demonstrated that the group receiving the aromatherapy had a significant reduction in anxiety score after 4 weeks of intervention, compared to the control group The result of the current study was also consistent with the study conducted by Marofi et al (1994) conducted with the aim of comparing the effect of the rose flower, fragrant geranium, and sweet almond oil on the severity of pain after pediatric surgery. Children's pain was very intense while entering the treatment section and before the intervention in all three groups, however, after applying the intervention in the two groups of aromatherapy with the rose flower and fragrant geranium has been effective in pain relief compared to sweet almond oil (as a placebo).…”
Section: Discussionsupporting
confidence: 92%
“…The Damask Rose, an indigenous plant of Iran, is one of the 308 species of the Rose family. It is being used to improve physical and mental health since ancient times (Barati et al 2016). This plant has soothing, sedative, anticonvulsant, antispasmodic, antibacterial, and antiviral effects and contains vitamins (A, C, B1, B2, B3, and K), citric acid, pectin, flavonoid, and carotenoid (Bikmoradi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated beneficial effects of R. damascena essential oil on sleep disorders, depression, anxiety, and pain, which are some of the symptoms of PMS. An Iranian study showed that inhalation of R. damascena can reduce anxiety among patients undergoing hemodialysis. The ability of R. damascena essential oil to improve the symptoms of depression and sexual dysfunction owing to treatment with selective serotonin‐reuptake inhibitors was confirmed among patients with major depressive disorders .…”
Section: Discussionmentioning
confidence: 99%